2004
DOI: 10.1007/s11934-004-0087-6
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic sling options for stress urinary incontinence

Abstract: In the past decade, sling surgery has become the preferred technique for the management of female stress urinary incontinence. A greater understanding of the pathogenesis of stress urinary incontinence and a greater durability and effectiveness for sling surgery has allowed this technique to become the benchmark for treatment of female stress urinary incontinence. As a consequence, a multitude of products have been developed using various techniques and materials to perform sling surgery. This article reviews … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Autologous tissue slings generally are well tolerated, but the use of such materials requires an additional procedure and potentially longer recovery times. In a recent review of the literature by Bukkapatnam and Rodriguez [8], it was found that slings derived from human or animal donors had less durability than synthetic slings. Slings derived from humans and animals also carry the theoretical risk of transmission of infectious agents.…”
Section: Surgical Management Of Stress Urinary Incontinencementioning
confidence: 99%
See 1 more Smart Citation
“…Autologous tissue slings generally are well tolerated, but the use of such materials requires an additional procedure and potentially longer recovery times. In a recent review of the literature by Bukkapatnam and Rodriguez [8], it was found that slings derived from human or animal donors had less durability than synthetic slings. Slings derived from humans and animals also carry the theoretical risk of transmission of infectious agents.…”
Section: Surgical Management Of Stress Urinary Incontinencementioning
confidence: 99%
“…Given these concerns, synthetic materials have emerged as the preferred option for urethral slings. Polypropylene is the most popular synthetic material in use today [8].…”
Section: Surgical Management Of Stress Urinary Incontinencementioning
confidence: 99%
“…At present, the mesh material most commonly used for sling surgery is polypropylene. 2 In 1996, Ulmsten et al were the first to report the use of polypropylene mesh around the mid-urethra. 3 Petros and Ulmsten described the tension-free vaginal tape (TVT) procedure based on the integral theory.…”
Section: Introductionmentioning
confidence: 99%